Experimental investigation of local bubble properties: Comparison to the sectional quadrature method of moments. Issue 10 (22nd June 2019) - Schäfer, Jan; Hlawitschka, Mark W.; Attarakih, Menwer M.; Bart, Hans‐Jörg
Abstract: In recent years, population balance models coupled to computational fluid dynamics have been used as a tool to model bubbly flows. In this work, we established a setup to measure the local size distribution, the velocity and orientation of bubbles in different zones of a bubble column. As a population balance model, we used the sectional quadrature method of moments for the first time in OpenFOAM to simulate the local change in the bubble size distribution and compared its results to the quadrature method of moments as well as to the experimental results. A satisfactory agreement between local experimental values of three investigated flow rates and simulations were found and enables the characterization of heterogeneous bubbly regimes as found in industrial reactive bubble columns.